Photorechargeable High Voltage Redox Battery Enabled by Ta3N5 and GaN/Si Dual‐Photoelectrode. Issue 26 (2nd May 2017) - Cheng, Qingmei; Fan, Weiqiang; He, Yumin; Ma, Peiyan; Vanka, Srinivas; Fan, Shizhao; Mi, Zetian; Wang, Dunwei
Abstract : Solar rechargeable battery combines the advantages of photoelectrochemical devices and batteries and has emerged as an attractive alternative to artificial photosynthesis for large‐scale solar energy harvesting and storage. Due to the low photovoltages by the photoelectrodes, however, most previous demonstrations of unassisted photocharge have been realized on systems with low open circuit potentials (<0.8 V). In response to this critical challenge, here it is shown that the combined photovoltages exceeding 1.4 V can be obtained using a Ta3 N5 nanotube photoanode and a GaN nanowire/Si photocathode with high photocurrents (>5 mA cm –2 ). The photoelectrode system makes it possible to operate a 1.2 V alkaline anthraquinone/ferrocyanide redox battery with a high ideal solar‐to‐chemical conversion efficiency of 3.0% without externally applied potentials. Importantly, the photocharged battery is successfully discharged with a high voltage output. Abstract : A dual‐photoelectrode system based on a Ta3 N5 nanotube photoanode and a GaN nanowire/Si photocathode enables the unassisted photocharge of a 1.2 V aqueous anthraquinone/ferrocyanide redox battery. The measured photovoltage of 1.4 V is the highest for similar experiments. Together with the high operating photocurrent densities, these photoelectrodes promise a route toward efficient solar rechargeable redox batteries.